2009
DOI: 10.1128/jcm.00338-09
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Treatment Response of Periodontally Diseased Patients Infected with the JP2 Clone ofAggregatibacter(Actinobacillus)actinomycetemcomitans

Abstract: This longitudinal study evaluated the response to periodontal treatment by subjects infected with either JP2 (n ‫؍‬ 25) or non-JP2 (n ‫؍‬ 25) Aggregatibacter (Actinobacillus) actinomycetemcomitans. Participants were treated during the first 4 months by receiving (i) scaling and root planing, (ii) systemic antibiotic therapy, and (iii) periodontal surgery. Probing depth (PD), clinical attachment level (CAL), and gingival and plaque indices (GI and PI, respectively) were monitored at baseline and at 12 months, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 45 publications
5
42
0
1
Order By: Relevance
“…Alternatively, some of the adolescents may have developed mild disease due to transient infection with the JP2 clone, as it has been found that over a 2-year period approximately half of this age group was temporarily colonized [36], whereas those persistently infected are supposed to develop more severe disease over time, as presumed for the slightly older patient sample included in the present study. In support of this, elimination of the JP2 clone has been shown to correlate with diminishing disease activity [37]. An association between the presence of the JP2 clone of A. actinomycetemcomitans and severity of disease among young adults with AgP is in agreement with results from a previous study on a Brazilian population, where the JP2 clone is also endemically present [26].…”
Section: Discussionsupporting
confidence: 59%
“…Alternatively, some of the adolescents may have developed mild disease due to transient infection with the JP2 clone, as it has been found that over a 2-year period approximately half of this age group was temporarily colonized [36], whereas those persistently infected are supposed to develop more severe disease over time, as presumed for the slightly older patient sample included in the present study. In support of this, elimination of the JP2 clone has been shown to correlate with diminishing disease activity [37]. An association between the presence of the JP2 clone of A. actinomycetemcomitans and severity of disease among young adults with AgP is in agreement with results from a previous study on a Brazilian population, where the JP2 clone is also endemically present [26].…”
Section: Discussionsupporting
confidence: 59%
“…The JP2 clone is attributed to descendants of North African populations, but is also prevalent in LAgP patients from other geographical locations (32, 33). It has been shown that A. actinomycetemcomitans JP2 is associated with initiation of periodontal tissue attachment loss (34), and eradication of JP2 provides better outcomes of periodontal treatment (3537). …”
Section: Discussionmentioning
confidence: 99%
“…Improving our knowledge of host cytokine regulation in response to bacterial challenge is fundamental to understanding the clinical course of the disease and developing novel treatment strategies for periodontitis (38,39). The clinical impact of LDD in modulating MMP activity is well-described, but its impact on the production of cytokines by monocytes is incomplete.…”
Section: Introductionmentioning
confidence: 99%